Marking time among the Ch’orti’ Maya: an expressive act of culture - Kerry Hull (Journal de la Société des Américanistes)
The indigenous population of Ch’orti’ Maya of southern Guatemala make use of many natural phenomena to identify and mark time. In this study I explain how Ch’orti’ organize and define the time for ceremonial, agricultural, and other purposes through the careful use of astronomical calculations and observations. I also show how time is divided and conceptualized within a day, and the specificity of these divisions in Ch’orti’. Furthermore, I argue that various lengths of time are of special importance for Ch’orti’ and dictate the duration of rituals, some of which could be based on corn farming cycles. Finally, I propose that several aspects regarding the notion of time among the Ch’orti’ have their roots in the ancient Classic Maya period.